THE IMPORTANCE OF A CONTINGENCY PLAN: FOR RESIDENTS OF VILA BOM JESUS ​​IN THE MUNICIPALITY OF CANAÃ DOS CARAJÁS-PA IN CASES OF DAM BREAK" - Pimentel da Silva, Helton (Revista Gênero e Interdisciplinaridade, 2024)
The dissertation titled “The Importance of a Contingency Plan: For the Residents of Vila Bom Jesus in the Municipality of Canaã dos Carajás-PA in Cases of Dam Rupture” addresses the urgent need for an effective contingency plan for this vulnerable community. The social relevance of the topic is unquestionable, given the increasing incidence of natural and technological disasters. The Brumadinho tragedy in 2019 highlighted the devastating consequences of dam failures, underscoring the importance of preventive measures. This study aims to examine the effectiveness of current contingency plans and propose recommendations to improve the preparedness and resilience of Vila Bom Jesus residents. Specific objectives include analyzing the structure of existing plans, assessing community perception, and proposing strategies for continuous improvement. The methodology used is based on a literature review, with strict inclusion and exclusion criteria to ensure the relevance and quality of the analyzed articles. The thematic analysis of the data facilitates the identification of patterns and critical elements for the development of effective plans. The results reveal that although contingency plans exist, the lack of knowledge and adequate preparation among residents compromises their effectiveness. Anderson Vasconcellos Amaral’s research highlights the transformation of Canaã dos Carajás landscapes due to mining and agriculture, and the social and environmental implications of these activities. The dissertation concludes that contingency plans need to be continuously reviewed and updated, incorporating new information and best practices. The contributions of this study are significant for the protection of vulnerable communities, providing practical guidelines that can be adapted to different contexts.